Spatial analysis of air pollution concentration (radon, humidity, VOCS) in the homes of the Mitham Al-Tammar neighborhood in Kufa - Ali Hassan Salam; Mazhar Abdul Hamid Raghad; Nafea Yousif Saja; Saeed jassim Ali (E3S Web of Conferences)
The study aims to determine the concentrations of radon, humidity, and CO2 in residences within the Mitham Al-Tammar neighbourhood of Kufa, utilising an Airthings 2960 Wave Plus device in the living rooms of each household. The concentration of radon varied, with a minimum value of 13 ± 3.9 Bq/m3 and a maximum value of 90 ± 5.8 Bq/m3, yielding an average rate of 35.8 ± 4.889 Bq/m3. The concentrations of total VOCs in residences ranged from 69.26 ppb to 810.14 ppb, with a mean of 321.4855 ± 40.4. The humidity percentages exhibited a minimum concentration of 51.68% and a maximum of 122.97%, averaging 76.594 ± 4.298. The concentrations of volatile organic compounds and humidity in the majority of residences exceeded the thresholds established by the World Health Organization and the US Environmental Protection Agency. This serves as proof that these dwellings lack adequate indoor air quality.